2015
DOI: 10.1007/s10151-015-1396-0
|View full text |Cite
|
Sign up to set email alerts
|

Implantation of SphinKeeperTM: a new artificial anal sphincter

Abstract: IntroductionA new artificial anal sphincter, SphinKeeperTM, was devised with the aim to treat fecal incontinence (FI) by implanting specifically designed self-expandable prostheses into the intersphincteric space. Preliminary data concerning the procedure feasibility and prosthesis localization at 3 months are presented.MethodsSphinKeeperTM prostheses in the native state are dehydrated, thin, solid cylinder (length 29 mm, diameter 3 mm), changing their state (shorter—length 23 mm, thicker—diameter 7 mm—and sof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(81 citation statements)
references
References 21 publications
2
76
1
Order By: Relevance
“…SK implantation was performed as described previously. Follow‐up visits were scheduled at 3, 6 and 12 months, and annually thereafter.…”
Section: Methodsmentioning
confidence: 99%
“…SK implantation was performed as described previously. Follow‐up visits were scheduled at 3, 6 and 12 months, and annually thereafter.…”
Section: Methodsmentioning
confidence: 99%
“…Publications on the Sphinkeeper are limited. Ratto et al [24] treated 10 patients with SK and followed them up for 3 months. The study demonstrated that the SK, with its larger prostheses than that of GK, is safe and effective.…”
Section: Resultsmentioning
confidence: 99%
“…When the injection is placed adjacent to an identifiable IAS defect, a better degree of anal canal sealing may be obtained through improvement in the configuration and symmetry of the anal canal [7]. Ratto argues that GK and SK, being embedded within the intersphincteric space, thereby pushing the EAS outwards and the IAS inwards, 'may improve sphincter contractility by increasing sarcomere length as well as increase the length of the anal canal and provide a powerful "bulking effect"' [24].…”
Section: Discussionmentioning
confidence: 99%
“…Devices, which require a partially functioning continence organ and reinforce the functionality of the sphincter muscles, are summarized together selected Refs. 8 , 9 , 36 , 48 , 49 in Table 1 . The sacral nerve stimulation (SNS) has become a standard operative procedure for the treatment of fecal incontinence.…”
Section: Overview Of Systems To Treat Incontinencementioning
confidence: 99%
“… Material (examples) Working principle Outcomes Relevance/Status Bulking agents (injected or implanted materials incl. SphinKeeper™) Collagen Autologous fat Silicone elastomers Teflon © Ceramic-microspheres Polyacryloniterile 48 , 49 Increases the volume around the anal canal, augment the passive closure pressure; self-expandable inter-sphincter prosthesis Success rates: 23–95% over a 3–19 month observational period 36 Success of placebo injections leads to success rates reaching 27% 36 Improvement in symptoms at least in the first year Small sample sizes and lack of long term studies do not permit general conclusions about safety and effectiveness 36 Slings (incl. FENIX ® ) Fascia Tendon Silk Nylon Teflon © Silicone Anal encirclement by bands.…”
Section: Overview Of Systems To Treat Incontinencementioning
confidence: 99%